Effect of levels organic fertilizers and kinds of Bio-feritilizers in characterical of two classes of Okra plant ( Abelmoschus esculentus L.) growning in the plastic house - Ahmed Salam Jwar; Razzaq G. Neghamish (University of Thi-Qar Journal of agricultural research, 2021)
The experiment was carried out for the agricultural season 2020-2021 under unheated greenhouse conditions at the Agricultural Research Station of the Department of Horticulture and Garden Engineering / College of Agriculture - University of Dhi Qar, studying the effect of levels of organic and biological fertilizers on the growth and yield of two okra varieties (Al-Hussainawi, Petra). The experiment was carried out with three factors: the first cultivar includes two okra cultivars (Al-Hussainawi A, Petra B), the second sheep manure with four levels O0 without addition, O1 (2.5 kg experimental unit), O2 (5 kg experimental unit) and O3 (7.5 kg experimental unit) and the third is a mixture of bio-fertilizer And at four levels: O0 without addition, A(Azo.) (Azotobacter chroococcum): at a concentration of 1.1×109, B(Pseu.): (Pseudomonas flourescens) at a concentration of 3.6×109 and C (Azo.+Pse.): (Azotobacter chroococcum + Pseudomonas flourescens) at a concentration. 4.7 × 109 The arithmetic averages were compared according to the LSD Least Significant Difference test at a probability level of 0.05. The results can be summarized as follows: It showed the superiority of the Husseinawi okra variety over the Petra okra variety in the leaf content of carbohydrates and phenols in the fruits, which amounted to (12.448 mg 100 gm-1, 2.132%). ) respectively. While the Petra cultivar was superior in the content of leaves of chlorophyll and a decrease in the content of the leaves of carotene and proline, it reached (69.615 mg 100 gm-1, 1.882 mg 100 gm-1, 190.0 microgram g-1). With regard to the organic fertilizer, the treatment O3 (7.5 kg experimental unit) for Al-Hussainawi variety was superior in the content of leaves of chlorophyll and phenols in the fruits, it amounted to (74,729 mg 100 gm-1, 2.742 %), while the Petra variety excelled in the content of carbohydrates and the low content of the leaves of carotene and proline. It reached (14,394 mg 100 g-1, 0.951 mg 100 g-1, 142.9 mcg g-1) respectively. As for the biofertilizer, the treatment C (Azo.+Pse.) was superior in the leaves content of chlorophyll and carbohydrates, and the leaves content of carotene, proline and phenols in the fruits was (72,555 mg 100 g-1, 13.683 mg 100 g-1, 0.974 mg 100 g-1, 156.7 micrograms g-1, 2.534%) respectively. As for the effect of the bilateral interaction between okra cultivars and biofertilizer types, the BC (Azo.+Pse.) treatment was superior to the chlorophyll content of leaves and the decrease in the leaves’ content of carotene and proline, it amounted to (72,996 mg 100 g-1, 0.762 mg 100 g-1, 136.2 micrograms g-1), while the AC (Azo.+Pse.) treatment excelled in the leaves content of carbohydrates and phenols in fruits, it reached (13.878 mg/100 gm-1, 2.576 %), respectively. The bilateral interaction between organic and biofertilizers showed the superiority of O3 C (Azo.+Pse.) treatment in the leaves content of chlorophyll and carbohydrates, and the decrease in the leaves’ content in carotene, proline and phenols in fruits, it amounted to (77,065 mg 100 g-1, 15.722 mg 100 g-1, 0.297 mg (100 gm-1, 121.6 mcg g-1, 3.4088%) respectively. The triple interactions showed a significant effect on most of the studied traits.